Industrial debate. Conceptions of industrial protection policy between Peru: 1935 - Lobo Collantes, Juan Franco (2011)
The ability to diversify our economy and into the path of industrialization, is part of a debate on the political agenda that seeks no longer argue about whether to industrialize or not, but rather how we are going to do. In this analysis, the business sector to seek input in this process is rarely taken into account. In that sense, this paper seeks to contribute to this analysis from a historical perspective, going into 1935. This year is chosen because the main analysis is based on an article written in that year published by the National Society of Industries. This text contains interviews and industrialists from the time we come to their conception of protectionism. The different views on this policy and bel should explain what these different approaches will be the central analysis of the article.